Dance teaching methods and curriculum design. - Kassing, Gayle, ....-; Jay, Danielle M., ....- (Champaign : Human Kinetics, 2003)
Inhoudsopgave (verkort) Part I: Dance Pedagogy: What You Need to Know About Teaching and Learning Dance Chapter 1. Envisioning Dance Education Chapter 2. Teaching Dance and Cross-Disciplinary Knowledge Chapter 3. Observing and Analyzing the Teaching and Learning Situation Chapter 4. Guiding Students in Learning DanceChapter 5. Understanding Dance Teaching Methods Chapter 6. Organizing and Managing the Dance Class Chapter 7. Analyzing the Learner and the Learning Environment Chapter 8. Categorizing Dance Forms and Their Artistic Demands Part II: Implementing Dance Pedagogy: What You Need to Do to Create a Dance Curriculum Chapter 9. Developing the Lesson Plan Chapter 10. Selecting the Appropriate Assessment Tools for Dance Chapter 11. Writing and Delivering the Lesson Plan Chapter 12. Creating a Curriculum Chapter 13. Sample Units for Dance Forms
Keywords: Dans -- Opleiding